An empirical look at the effect of service quality on online shopping customer satisfaction in Indonesia - Risanty Risanty; Sambas Ade Kesuma; Juwita Agustrisna; May Hana Bilqis (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
The main purpose of this study is to examine the relationship between service quality and online shopping customer satisfaction in Indonesia. This study is a quantitative and cross-sectional study with a survey method. This study's online shopping customers consist of undergraduate and postgraduate students in the Accounting Department of Universitas Sumatera Utara. The study used Likert scale questionnaires distributed to 400 respondents, and 295 questionnaires were obtained for data analysis. The study found that service quality has a positive and significant relationship with customer satisfaction. The study reveals that the elevation of excellent service quality on online shopping is the best solution for online shopping vendors to obtain customer satisfaction.